Photoinduced alkyl group exchange of ethylzinc alkoxides: X-ray crystal structure of an iodomethylzinc methoxide - Charette, A; Beauchemin, A; Francoeur, S; Belanger-Gariepy, F; Enright, GD (Chemical communications (Cambridge, England), 2002)
Irradiation of a solution of ethyl zinc alkoxides and CH2I2 leads to clean formation of iodomethylzinc alkoxides; these intermediates are important species generated in stereoselective cyclopropanation processes; no alkyl group exchange is observed in the absence of irradiation; the solid-state structure of (MeO)(8)Zn-7(CH2I)(6) is also reported.